2006
DOI: 10.1002/mmce.20119
|View full text |Cite
|
Sign up to set email alerts
|

Benchmark of full Maxwell 3D electromagnetic field solvers on an SOIC8 packaged and interconnected circuit

Abstract: The MAGMAS3D full Maxwell electromagnetic field solver developed at Katholieke Universiteit. Leuven is benchmarked with several commercially available solvers in the analysis of a complete industry-standard SOIC8 (single-outline integrated circuit with eight leads) circuit, packaging, and interconnection topology. The benchmark deals with predicted results as well as computer speed and memory. The benchmark description and results should give practicing engineers valuable insights into (at least part of) the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Remaining differences are again probably due to different excitation models and de-embedding schemes. This shortcoming did not influence the results in the parallel benchmark of an electrically small electric circuit [3] (Fig. 5).…”
Section: Simulated Versus Measured Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Remaining differences are again probably due to different excitation models and de-embedding schemes. This shortcoming did not influence the results in the parallel benchmark of an electrically small electric circuit [3] (Fig. 5).…”
Section: Simulated Versus Measured Resultsmentioning
confidence: 87%
“…Leuven [2], as an electrically large radiating and resonating benchmark structure. It was conducted in parallel with a benchmark performed on a geometrically complex but electrically small packaged and interconnected electrical circuit [3], to bring into the forefront the capabilities, limitations and performance of some of the solvers currently offered on the full-wave 3D EM simulation market in each specific area of application. This paper describes a "realistic" software benchmark.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, such an extensive benchmark study over a large variety of solvers and for several structures was only reported in [50], which is the core paper providing most of the basic material for this section. In [51] and [52] a comparable analysis was conducted using four different solvers, but only for one structure. An accuracy and speed benchmark on six EM solvers was presented in [53] for four different antennas, but the physical link between simulation results for a specific antenna problem and the applied solution method has not yet been generally established.…”
Section: Benchmarkingmentioning
confidence: 99%
“…The study does not include the comparison of Graphical User Interfaces (GUI), price/performance ratio, user friendliness, etc.. To our knowledge, such an extensive benchmark study over a large variety of solvers and for several structures was not yet documented. In [1] and [2] a comparable analysis was conducted using four different solvers, but only for one structure. An accuracy and speed benchmark on six EM solvers was presented in [3].…”
Section: Introductionmentioning
confidence: 99%